Substituição do concentrado por níveis crescentes de silagem de gliricídia na alimentação de cordeiros - Silva, Lucas Feitosa (2012)
This study aimed to evaluate the partial substitution of concentrate for gliricidia silage (Gliricidia sepium) in diets of lambs during growth on nutrient intake, daily weight gain, and feed conversion. Were used 27 Santa Inês lambs not castrated, weaned, with an average initial live weight of 14.5 kg and aged approximately four months from the flock of Embrapa Semiárido‟. The animals were subjected to four treatments in relation to dry matter substitution, 1 - corn silage (60%) + concentrate (40%) 2 - corn silage (60%) + gliricidia silage (13.3% ) + concentrate (26.7%), 3 - corn silage (60%) + gliricidia silage (26.7%) + concentrate (13.3%) and 4 - corn silage (60%) + silage Gliricídia (40%). The experimental design was randomized with four treatments and variable number of 19 repetitions and the experimental unit was one lamb. The live weights were similar among the four different treatments in the initial weighing, showing a significant difference only in the final weight, where the lambs that were fed with diets containing concentrate, regardless of the level, showed similar or higher performance (P> 0.05) than lambs receiving only gliricidia. The daily weight gain of lambs was higher for those fed concentrate than other treatments. For body weight before and after fasting, treatments that consumed concentrate were higher (P <0.05) than the treatment without addition of concentrate, except for the exclusive treatment between the silage and the treatment they consumed fewer concentrated in body weight during fasting (P> 0.05) Losses in the fasting were not different (P> 0.05) between treatments. The hot and cold carcass weight were higher (P <0.05) for the treatment that did not consume gliricidia silage and in the treatment that consumed 26.7% concentrate related to the treatment that consumed silage gliricidia, and the treatment consumed 13.3% of concentrate. The hot and cold carcass yield were different (P <0.05) between treatments, where the two treatments who consumed more concentrate showed higher values than the others. Regarding the commercial cuts of carcasses treatments consuming concentrate had higher absolute weights, however, in the percent of weight, there was no significant difference (P> 0.05).